KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DI MTS AL-MUHAJIRIN LAMPUNG UTARA - Zainal Abidin; Agus Jatmiko; Ilhami Ilhami (STKIP Pesisir Selatan, 2026)
This study aims to analyze the application of transformational leadership by the school principal in enhancing teacher competencies at MTs Al-Muhajirin in North Lampung. This study employs a qualitative approach with a descriptive design to gain an in-depth understanding of the phenomenon within its natural context. Data analysis was conducted interactively through data reduction, data presentation, and drawing conclusions. Data validity was tested using source and technique triangulation. The research results indicate that the principal’s transformational leadership plays a significant role in enhancing teachers’ competencies through four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. The principal’s exemplary leadership enhances teachers’ professionalism and discipline; the motivation provided strengthens work ethic and commitment; intellectual stimulation drives learning innovation; and individual consideration improves performance and fosters teachers’ potential development. The novelty of this study lies in the comprehensive strengthening of transformational leadership implementation across all its dimensions, which has been proven to create a conducive, collaborative, and sustainable work environment, thereby contributing to improved learning quality.